2015
DOI: 10.1074/jbc.m115.637470
|View full text |Cite
|
Sign up to set email alerts
|

A-kinase Anchoring Protein 79/150 Recruits Protein Kinase C to Phosphorylate Roundabout Receptors

Abstract: Background: A-kinase anchoring proteins position signaling enzymes to control neuronal phosphorylation events. Results: Biochemical and cellular approaches confirm that the AKAP79/150 signaling complex interfaces with the cytoplasmic tail of Roundabout (Robo) receptors. Conclusion: AKAP79/150-associated protein kinase C facilitates the phosphorylation of Ser-1330 on the Robo3.1 isoform. Significance: Kinase anchoring is a mechanism to control the phosphorylation of Robo3.1 within macromolecular assemblies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Lastly, a proximity ligation assay (PLA) was used to pinpoint p766-Gravin association with either kinase during the cell cycle ( Figure 2E–H ). This approach combines antibody recognition with amplification of a DNA hetero-duplex to mark discrete protein–protein interaction pairs that reside within 40–60 nm of each other ( Samelson et al, 2015 ). Quantification of PLA puncta indicated that p766-Gravin/Aurora A sub-complexes was enhanced 3.86-fold during metaphase when compared to interphase cells ( Figure 2E,F ).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, a proximity ligation assay (PLA) was used to pinpoint p766-Gravin association with either kinase during the cell cycle ( Figure 2E–H ). This approach combines antibody recognition with amplification of a DNA hetero-duplex to mark discrete protein–protein interaction pairs that reside within 40–60 nm of each other ( Samelson et al, 2015 ). Quantification of PLA puncta indicated that p766-Gravin/Aurora A sub-complexes was enhanced 3.86-fold during metaphase when compared to interphase cells ( Figure 2E,F ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, functional analyses reveal that loss of this anchoring protein promotes a redistribution of its enzyme binding partners including protein kinase A and calcineurin with concomitant changes in a variety of vital cellular processes including excitatory synaptic transmission, glucose homeostasis and vascular tone (13; 31; 41; 42). However, much less is known about the AKAP150-calcineurin interface in the heart (4346).…”
Section: Resultsmentioning
confidence: 99%
“…They include cellular (protein inhibitors) and pharmacological inhibitors. Although numerous endogenous proteins may have potential to inhibit calcineurin or NFAT activities, only four are well-characterized: (i) A-kinase anchoring protein 79 (AKAP79), a scaffold protein that prevents calcineurin-substrate interactions [ 96 , 97 ]; (ii) calcineurin inhibitor (CAIN) or calcineurin-binding (CABIN) proteins, which block calcineurin activity [ 98 , 99 ]; (iii) calcineurin homologous protein (CHP); and (vi) modulatory calcineurin-interacting proteins (MCIP1–3), which prevent NFAT nuclear import by preventing its phosphorylation [ 94 , 100 103 ].…”
Section: Calcineurin/nfat Pathwaymentioning
confidence: 99%